Transcriptome analysis revealed the drought-responsive genes in Tibetan hulless barley. (December 2016) - Zeng, Xingquan; Bai, Lijun; Wei, Zexiu; Yuan, Hongjun; Wang, Yulin; Xu, Qijun; Tang, Yawei; Nyima, Tashi
Abstract Background Hulless barley, also called naked barley, is an important cereal crop worldwide, serving as a healthy food both for human consumption and animal feed. Nevertheless, it often suffered from drought stress during its growth and development, resulting in a drastic reduction in barley yields. Therefore, study on molecular mechanism of hulless barley drought-tolerance is very important for increasing barley production. To investigate molecular mechanism of barley drought-resistance, this study examined co-regulated mRNAs that show a change in expression pattern under early well water, later water deficit and finally water recovery treatments, and to identify mRNAs specific to water limiting conditions. Results Total of 853 differentially expressed genes (DEGs) were detected and categorized into nine clusters, in which VI and VIII were apparently up-regulated under low relative soil moisture content (RSMC) level. The majority of genes in these two clusters was relevant to abiotic stress responses in abscisic acid (ABA) dependent and independent signaling pathway, includingNCED, PYR/PYL/RCAR, SnRK2, ABF, MYB/MYC, AP2/ERF family, LEA andDHN . In contrast, genes within clusters II and IV were generally down-regulated under water stress; cluster IX genes were up-regulated during water recovery response to both low and high RSMC levels. Genes in implicated in tetrapyrrole binding, photosystem and photosynthetic membrane were the most affected in cluster IX. Conclusion Taken together, our findings indicate that the responses of hulless barley to drought stress shows differences in the pathways and genes activated. Furthermore, all these genes displayed different sensitivities to soil water deficit and might be profitable for future drought tolerance improvement in barley and other crops.